Transparency in Village Fund Financial Management - Ramos Da Chrismas; Elias Mite; Edoardus E Maturbongs; Imelda C Laode; Dapot Pardamean Saragih; David Laiyan (Department of State Administration - Musamus University, 2020)
The launch of village funds in Papua is always increasing every year given by the government, but on the other hand raises new problems regarding financial management and transparency. This study aims to provide new thinking about financial transparency of village funds suitable for the Papua region. The method used is literature study, and the results of this study are transparency that must be carried out, namely the provision and access of clear information about planning, implementation procedures and accountability (billboards, website, Facebook), the existence of deliberations involving the community and indigenous peoples / Chair Adat, Openness of the management process, Supervision is carried out by the whole community, Transparency of information on Village Financial management documents, Continual socialization and training from the government to the Village for effective management of the Village Fund, and Village Fund Assistance is actually recruited from people who have very high self-integrity.